2019
DOI: 10.1111/jopr.13024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bonding and Rebonding on the Shear Bond Strength of Two‐Piece Implant Restorations

Abstract: Purpose To evaluate the rebonding strength of ceramics to titanium alloy after disassembling by heat treatment. Materials and Methods A total of 40 titanium alloy (titanium‐6 aluminum‐4 vanadium) disks (4.0 × 6.6 mm) and 20 zirconia (Lava Plus) disks were manufactured using computer‐aided design and computer‐aided manufacturing (CAD/CAM) technology. Twenty heat‐pressed lithium disilicate glass‐ceramic (IPS e.max Press LT) disks were fabricated and used as controls. Bonding protocol for each specimen surface wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…This study found that heat oxidation of titanium at 500 ˚C for 5 minutes does not affect resin cement bond strength to zirconia, which is consistent with the previous study [ 8 ]. However, a study found that heating a cp titanium disk over 400˚C can decrease resin bond strength according to the thickening of the oxide layer [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found that heat oxidation of titanium at 500 ˚C for 5 minutes does not affect resin cement bond strength to zirconia, which is consistent with the previous study [ 8 ]. However, a study found that heating a cp titanium disk over 400˚C can decrease resin bond strength according to the thickening of the oxide layer [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…Dental laboratories can separate the crown from the titanium abutment using constant dry heat to break cement retention. A crown can be remade, then the separated abutment can be cleaned and recemented resulting in the desired restoration [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another investigation on the adhesion of five different ceramics and ceramic-like materials with three different resin types of cement, adhesive and cohesive failures after shear bond strength testing were observed at similar frequencies [ 10 ]. In another study examining the bond strength of lithium disilicate ceramics and zirconium ceramics with two-piece abutments, mixed failure (adhesive and cohesive) was observed in the lithium disilicate samples [ 31 ]. In this study, mixed failure was found in all the specimens, similar to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, in resin cement, although thermocycling decreased the values of tensile strength, this did not promote a significant difference. This may be due to the use of adhesive systems that, in addition to the surface alteration of Zr with AL 2 O 3 blasting, made the adhesion more stable even after an aging process, as shown in Figure 2 in the confidence interval line 15,28 .…”
Section: Discussionmentioning
confidence: 99%